Intellectual disability-associated dBRWD3 regulates gene expression through inhibition of HIRA/YEM-mediated chromatin deposition of histone H3.3. - Chen, W.Y.; Shih, H.T.; Liu, K.Y.; Shih, Z.S.; Chen, L.K.; Tsai, T.H.; Chen, M.J.; Liu, H.; Tan, B.C.; Chen, C.Y.; Lee, H.H.; Loppin, B.; et al. (EMBO Reports, 2015)
Many causal mutations of intellectual disability have been found in genes involved in epigenetic regulations. Replication-independent deposition of the histone H3.3 variant by the HIRA complex is a prominent nucleosome replacement mechanism affecting gene transcription, especially in postmitotic neurons. However, how HIRA-mediated H3.3 deposition is regulated in these cells remains unclear. Here, we report that dBRWD3, the Drosophila ortholog of the intellectual disability gene BRWD3, regulates gene expression through H3.3, HIRA, and its associated chaperone Yemanuclein (YEM), the fly ortholog of mammalian Ubinuclein1. In dBRWD3 mutants, increased H3.3 levels disrupt gene expression, dendritic morphogenesis, and sensory organ differentiation. Inactivation of yem or H3.3 remarkably suppresses the global transcriptome changes and various developmental defects caused by dBRWD3 mutations. Our work thus establishes a previously unknown negative regulation of H3.3 and advances our understanding of BRWD3-dependent intellectual disability.